Identification of a Pyroptosis-Related Gene Signature for Predicting the Immune Status and Prognosis in Lung Adenocarcinoma - Gong, Zetian; Li, Qifan; Yang, Jian; Zhang, Pengpeng; Sun, Wei; Ren, Qianhe; Tang, Junjie; Wang, Wei; Gong, Hui; Li, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Pyroptosis, a kind of programmed cell death characterized by the rupture of cell membranes and the release of inflammatory substances, was essential in the occurrence and development of cancer. Considerable studies have demonstrated pyroptosis is involved in the biological process of various cancers. However, the role of pyroptosis in lung adenocarcinoma (LUAD) remains unclear. The purpose of this study was to explore the prognostic role of pyroptosis-related genes (PRGs) and their relationship with TIME in LUAD. Methods: Gene expression profiles and clinical information were downloaded from The Cancer Genome Atlas (TCGA) and GEO databases. A prognostic PRG signature was established in the training set and verified in the validation sets. Functional enrichment and immune microenvironment analyses related to PRGs were performed and a nomogram based on the risk score and clinical characteristics was established. What’s more, quantitative real-time PCR (qRT-PCR) analysis was applied to verify the potential biomarkers for LUAD. Results: A prognostic signature based on five PRGs was constructed to separate LUAD patients into two risk groups. High-risk patients had worse prognosis than patients in the low-risk group. The signature was identified to be independent by the cox regression analyses and obtained the largest area under the curve (AUC = 0.677) in the ROC. Functional enrichment and immune microenvironment analyses demonstrated that the immune status was significantly different in the two subgroups and immunotherapy may be effective to the high-risk group. Furthermore, qRT-PCR analysis verified that serum PRKACA and GPX4 could serve as diagnostic biomarkers for LUAD. Conclusion: Overall, a risk signature based on five PRGs was generated, providing a novel perspective on the determinants of prognosis and survival in LUAD and a basis for the development of individualized regimes.